Peningkatan Hasil Belajar Peserta Didik Menggunakan Model Cooperative Learning Tipe Two Stay Two Stray di Kelas V Sekolah Dasar - Putri, Vianes Muliza; Indrawati, Tin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2022)
The purpose of this research is to describe the improvement student learning outcomes of integrated thematic learning by using cooperative learning model tipe two stay two stray at Grade V SDN 10 sungai pasak. Type of the research is classroom action research  by using qualitative and quantitative approach. The subjects of the research were teacher and 20 grade V students. Therefore, the cooperative learning model tipe two stay two stray could improve the students learning outcomes of integrated thematic learning. The results of lesson plan observation on cycle I was 80.55%, and cycle II was 94.44%. The observation of teacher on cycle I was 79,69% and cycle II was 90.63%. While, the improvement of students aspect on cycle I was 76,58% and cycle II was 90,63%. While the average student learning outcomes in the knowledge aspect is 75.3 to 90.1, and in the skill aspect it gets an average of 71.66 to 86.67.The purpose of this research is to describe the improvement student learning outcomes of integrated thematic learning by using cooperative learning model tipe two stay two stray at Grade V SDN 10 sungai pasak. Type of the research is classroom action research  by using qualitative and quantitative approach. The subjects of the research were teacher and 20 grade V students. Therefore, the cooperative learning model tipe two stay two stray could improve the students learning outcomes of integrated thematic learning. The results of lesson plan observation on cycle I was 80.55%, and cycle II was 94.44%. The observation of teacher on cycle I was 79,69% and cycle II was 90.63%. While, the improvement of students aspect on cycle I was 76,58% and cycle II was 90,63%. While the average student learning outcomes in the knowledge aspect is 75.3 to 90.1, and in the skill aspect it gets an average of 71.66 to 86.67.